Tratamento de águas residuárias da indústria de laticínios pelos processos combinados coagulação/floculação/adsorção/ultrafiltração utilizando semente de Moringa oleífera como coagulante - Schmitt, Dalila Maria Formentini (2011)
In Brazil, the dairy industry are mostly small and medium-sized and using conventional processing techniques coupled with the use of inorganic coagulants. Therefore, this sector needs special attention with regard to advanced techniques for treating their wastewater, in order to meet new environmental regulations and seek alternatives for reuse of treated water. Within this context, this study evaluated the effectiveness of treatment techniques based on principles of coagulation / flocculation using coagulant extracted from Moringa oleifera seed with salt solutions of KCl and NaCl 1.0 Molar, adsorption with Moringa oleífera seed as biosorbent and ultrafiltration with tubular ceramic membrane. The different techniques were evaluated individually and in combination, the efficiency of processes was assessed in terms of removal of parameters: apparent color, turbidity and COD. Among the techniques evaluated the best results were obtained with the combination of technique and the coagulation / flocculation / sedimentation for 60 min using 1500 ppm of coagulant extracted from Moringa oleífera with 1.0 Molar KCl solution combined with ultrafiltration technique at a pressure of 2 bar. This combination of techniques has achieved a 99.9% removal of apparent color and turbidity, and 98.5% of COD. Based on the results of Moringa oleífera was presented as a promising natural coagulant for the treatment of wastewater from the dairy industry. This technique combined with ultrafiltration can enable the reuse of water within the industry.